2013
DOI: 10.1371/journal.pone.0060248
|View full text |Cite|
|
Sign up to set email alerts
|

Can Insects Develop Resistance to Insect Pathogenic Fungi?

Abstract: Microevolutionary adaptations and mechanisms of fungal pathogen resistance were explored in a melanic population of the Greater wax moth, Galleria mellonella. Under constant selective pressure from the insect pathogenic fungus Beauveria bassiana, 25th generation larvae exhibited significantly enhanced resistance, which was specific to this pathogen and not to another insect pathogenic fungus, Metarhizium anisopliae. Defense and stress management strategies of selected (resistant) and non-selected (susceptible)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 51 publications
3
92
0
4
Order By: Relevance
“…Some studies reported a possible positive correlation between melanisation, PO activity, and tolerance to parasites and pathogens such as B. bassiana and M. anisopliae [59,60]. In our electron microscopy studies of the head region, we found that infection of M. brunneum blastospores triggers a melanisation response by Cx.…”
Section: Discussionsupporting
confidence: 60%
“…Some studies reported a possible positive correlation between melanisation, PO activity, and tolerance to parasites and pathogens such as B. bassiana and M. anisopliae [59,60]. In our electron microscopy studies of the head region, we found that infection of M. brunneum blastospores triggers a melanisation response by Cx.…”
Section: Discussionsupporting
confidence: 60%
“…This defense mechanism is found naturally (Dubovskiy et al, 2013a) or can be the outcome of experimental coevolution (Dubovskiy et al, 2013b), indicating that natural melanism in this species may have evolved as a heritable response to fungal infection.…”
Section: G Mellonella Is Susceptible To Entomopathogenic Fungi Andmentioning
confidence: 90%
“…To determine whether the insects could evolve to acquire resistance to the fungi, experimental coevolution was carried out using G. mellonella and B. bassiana (Dubovskiy et al, 2013b). A melanic G. mellonella population was selected over 25 generations for increased resistance towards B. bassiana.…”
Section: G Mellonella Is Susceptible To Entomopathogenic Fungi Andmentioning
confidence: 99%
“…However, although generalizations cannot be made, the cumulative effect is controlled by the weather, the active constituent of the insecticide, the chemical mode of action, and the M. anisopliae isolated to control M. fimbriolata (Dinardo-Miranda et al, 2004a;Loureiro et al, 2005). On other hand, the genetic constitution of the pest population (Quinelato et al, 2012), adaptations and mechanisms of insect resistance (Dubovskiy et al, 2013) may influence the efficiency of the control techniques.…”
Section: Conventional Sampling × New Sampling Methods: Between 15 Janumentioning
confidence: 99%